Health risk assessment at hydro cracker complex oil and gas company - Zulkifli Djunaidi (Majalah Kesehatan Indonesia, 2023)
The hydro cracker complex (HCC) operating area is one of the areas with the most use of chemicals, and several workers complain about the noise in that area. This research determines the level of health hazard risk through a health risk assessment (HRA) focusing on physical, chemical, and biological hazards in the HCC area aims to improve the health status of workers and as a basis for developing occupational health programs to minimize the risk of occupational diseases. This study used primary data (walkthrough survey, interviews, heat stress measurements, noise, lighting, chemicals, fungi, and bacteria) with a cross-sectional method referring to the International Council on Mining & Metals (ICMM). The dangers of gasses and chemicals are the most common hazard in the HCC area. Based on the risk assessment, five hazard ratings with the highest risk were obtained, namely noisy environment (extreme), H2S gas (extreme), heat stress (extreme), NH3 gas (high risk), and hydrocarbon vapors (high risk). Existing controls and control recommendations must be applied comprehensively and consistently so that the company can accept the resulting residual risk value. Abstrak: Area operasi hydro cracker complex (HCC) merupakan salah satu area yang paling banyak menggunakan bahan kimia, dan beberapa pekerja mengeluhkan kebisingan di area tersebut. Penelitian ini menentukan tingkat risiko bahaya kesehatan melalui health risk assesment (HRA) yang berfokus pada bahaya fisik, kimia, dan biologi di area HCC yang bertujuan untuk meningkatkan status kesehatan pekerja dan sebagai dasar untuk mengembangkan program kesehatan kerja untuk meminimalkan risiko penyakit akibat kerja. Penelitian ini menggunakan data primer (walkthrough survey, wawancara, pengukuran tekanan panas, kebisingan, pencahayaan, bahan kimia, jamur, dan bakteri) dengan metode cross-sectional mengacu pada International Council on Mining & Metals (ICMM). Gas dan bahan kimia merupakan bahaya yang paling umum terjadi di kawasan HCC. Berdasarkan penilaian risiko diperoleh lima peringkat bahaya dengan risiko tertinggi, yaitu lingkungan bising (ekstrim), gas H2S (ekstrim), tekanan panas (ekstrim), gas NH3 (risiko tinggi), dan uap hidrokarbon (risiko tinggi). Pengendalian yang ada dan rekomendasi pengendalian harus diterapkan secara komprehensif dan konsisten agar perusahaan dapat menerima nilai residual risk yang dihasilkan.